DRUGS UTILIZATION STUDY IN NEONATAL SEPSIS IN TERTIARY CARE HOSPITAL - P, AGRAWAL; A, SINGHAL; VK, AGRAWAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The present study was taken up to evaluate the drug utilization pattern and adverse drug reactions (ADRs) seen in patients of neonatal sepsis admitted to sick newborn care unit of a tertiary care hospital in Uttarakhand. Methods: This was a prospective observational study. A suitable case record form was designed to collect all the necessary and relevant information. Data of 175 neonatal sepsis matching inclusion criteria were recorded. Pattern of prescription of drug for various diseases in sick newborns was analyzed. Information on ADR were analyzed. ADR was analyzed using Naranjo scale and the WHO causality assessment scale. Results: Blood culture was positive in 137 (78.29%) neonates. Staphylococcus aureus (45.26%) was the most common microorganism followed by Klebsiella pneumoniae (26.28%) and Escherichia coli (14.60%). Out of 137 blood culture-positive neonates, 30.66% were suffering from meningitis. Out of 38 blood culture-negative neonates, 63.16% were suffering from meningitis. Average number of drugs per encounter was 1.71. Percentage of drugs prescribed by generic name was 91%. Parenteral route was the most common route of drug administration. Ampicillin was the most common antimicrobial prescribed. Next common classes of drug used were vasopressor. Out of 10 (5.71%) ADRs identified, 70% were possible and 30% were doubtful as per Naranjo’s causality assessment scale. Case fatality rate was 27.42% during the course of study. Conclusion: Parenteral antibiotics (ampicillin plus gentamycin) and vasopressors remain the most commonly prescribed drugs in neonatal sepsis in sick newborn unit. The study concluded that doses and duration, for which drugs were used, were in accordance to AIIMS protocol for neonatal sepsis.